Fuzzy Logic and Geostatistical Techniques for Spatialization of Soil Texture in Region with Rough Terrains - Camarinha, P. I. M. [UNESP]; Trannin, I. C. B. [UNESP]; Simoes, S. J. C. [UNESP]; Bernardes, George de Paula [UNESP] (Elsevier B.V., 2011)
From the geotechnical standpoint, it is interesting to analyse the soil texture in regions with rough terrain due to its relation with the infiltration and runoff processes and, consequently, the effect on erosion processes. The purpose of this paper is to present a methodology that provides the soil texture spatialization by using Fuzzy logic and Geostatistic. The results were correlated with maps drawn specifically for the study area. The knowledge of the spatialization of soil properties, such as the texture, can be an important tool for land use planning in order to reduce the potential soil losses during rain seasons. (c) 2011 Published by Elsevier Ltd. Selection and peer-review under responsibility of Spatial Statistics 2011
Keywords: texture of soil; geostatistic; kriging; infiltration; watershed management; Southeast Brazil